2019
DOI: 10.1186/s13018-019-1452-y
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-tendon weakness contributes to chronic fatigue syndrome in Gaucher’s disease

Abstract: BackgroundChronic fatigue (CFg) is a prevalent symptom in Gaucher disease (GD) at diagnosis (79%) and remains in a quarter of patients after years of therapy. Bone abnormalities are present in over 70% and peripheral neuropathy in about 11% of the patients, which contributes to the disabling and debilitating complications. Our hypothesis is that other factors such as muscle-tendinous weakness could have influence in the development of CFg.MethodsWe have evaluated the fiber structure and elasticity of muscle-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Fatigue is certainly one of the most difficult symptoms to analyze, particularly in patients with GD1 [26], also due to the absence of a validated specific tool. Fatigue in GD1 is not exclusively explained by hematological alterations, such as anemia, and other causes should be explored [27]. Overall, laboratory parameters did not change over time, except hemoglobin concentration that improved, differently from what was reported by Chi and Amato [18].…”
Section: Discussionmentioning
confidence: 71%
“…Fatigue is certainly one of the most difficult symptoms to analyze, particularly in patients with GD1 [26], also due to the absence of a validated specific tool. Fatigue in GD1 is not exclusively explained by hematological alterations, such as anemia, and other causes should be explored [27]. Overall, laboratory parameters did not change over time, except hemoglobin concentration that improved, differently from what was reported by Chi and Amato [18].…”
Section: Discussionmentioning
confidence: 71%
“…Based on these features, sonoelastographic examination of the Achilles tendon has been performed in many diseases in the literature and the relationship between the disease and the measurements has been evaluated. [12][13][14][15][16][17] It has been concluded that in addition to rheumatological diseases, there are subclinical changes in sonoelastography in the Achilles tendon in metabolic and structural musculoskeletal system problems, which can be useful in predicting the prognosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These studies focused on evaluating the QoL of patients with GD and analyzing the influencing factors associated with the patients' QoL, both positive and negative. GD severely affects several major QoL dimensions [7,13,19,20,[30][31][32][33][34][35]. Patients with GD scored significantly worse than did the age-and sex-adjusted normal population on five of the eight SF-36 subscales (p < 0.05) [20].…”
Section: Cross-sectional Studies and Qualitative Researchmentioning
confidence: 99%